J.D Salinger’s Worldview as Reflected in The Catcher in the Rye: A Genetic Structuralism Analysis - Ahmad Priyono; Ida Puspita (Edumaspul: Jurnal Pendidikan, 2024)
Baby boomer generation in America is considered to have a brighter future compared to the previous generations. This generation was born after World War II and started a new life amidst the contestations of their time. Consequently, they are perceived as a selfish generation prioritizing individual interests, leading to a blurred sense of humanism among them. Through J.D. Salinger's work, The Catcher in the Rye, these issues are expressed by implementing Salinger's worldview on humanism. Therefore, this research aims to unveil Salinger's worldview as reflected in The Catcher in the Rye. To elaborate, the researcher utilizes the genetic structuralism theoretical framework by Lucien Goldmann. The results of this study yield several points. Firstly, the structure and structuration in the novel can be observed through the relationships between Holden Caulfield and other characters, as well as the relationship between Holden Caulfield and the nearby objects. Secondly, there exists homology between events in the real world of the baby boomer generation and those depicted in the novel. Thirdly, Salinger presents a worldview of humanism in The Catcher in the Rye.